National Institutional Structures, Transaction Cost Economizing and Competitive Advantage: The Case of Japan - Hill, Charles W. L. (Organization Science, 1995)
Japan’s economic success since World War II has been striking. Modern Japan was the first major industrial economy to emerge from outside the Western tradition. Economically devastated in 1945, by 1990 Japan had the world’s second largest economy and a GDP per head 20 percent greater than that of the United States. In this paper it is argued that one reason for Japan’s success is that the costs of achieving cooperation and specialization are lower in Japan than in the West. Cooperation and specialization have been acknowledged to have a beneficial impact upon productivity ever since Adam Smith wrote about cooperative specialization in the context of the division of labor. Modern economic theory, however, suggest that in a world of self-interested individuals the costs of achieving cooperation and specialization are substantial. In this paper it is argued that the cultural value system that Japan has inherited from its preindustrial past, and particularly the Tokugawa period, helps facilitate cooperation between individuals and encourages them to undertake productivity-enhancing investments in specialization. This lowers the costs of achieving cooperative specialization. In turn, the lower costs of achieving cooperative specialization have helped Japanese enterprises adopt practices such as self-managing work teams and long-term supplier relations that are consistent with obtaining a productivity-based competitive advantage in the world economy.